Redescription of Bagauda avidus (Hemiptera: Heteroptera: Reduviidae: Emesinae) with notes on other species of the genus in India - Joshi, Nikhil U.; Boyane, Swapnil S.; Ghate, Hemant V. (Zootaxa, 2022)
The thread-legged assassin bug Bagauda avidus Bergroth, 1903 (Hemiptera: Heteroptera: Reduviidae: Emesinae: Leistarchini), the type species of the genus Bagauda Bergroth, 1903, is redescribed based on light microscopic observations and scanning electron microscopy images. Additional five species of Bagauda occurring in India are briefly reviewed.